Identification and characterisation of micrornas involved in the pathogenesis of HIV–associated non-Hodgkin's lymphoma - Goolam Hoosen, Taahira (Division of Clinical Haematology, 2017)
Background: Since its discovery about three decades ago, the Human Immunodeficiency Virus (HIV) has claimed over millions of lives globally. Although our understanding of the mode of transmission and action of this causative agent for the Acquired Immune Deficiency Syndrome (AIDS) has increased through research, and treatment regimens developed and improved, in certain parts of the world the pandemic continues to expand. Sub-Saharan Africa, which is the epicentre of this global health concern, accounts for approximately 66% of the total number of individuals affected, with South Africa enduring the heaviest burden. South Africa has the world's largest antiretroviral therapy (ART) programme and as such, HIV infected people are living longer, and consequently the incidence of HIV co-morbidities has increased dramatically. HIV/AIDS defining cancers are such co-morbidities with Non- Hodgkin's lymphomas (NHL) being the second most common HIV-associated cancer. Diffuse Large B-cell lymphoma (DLBCL) and Burkitt's lymphoma (BL) are the main subtypes and both present aggressively in HIV positive patients with rapid progression. The use of highly active antiretroviral therapy (HAART) has decreased the incidence of DLBCL in HIV positive patients, however the prevalence of these cancers still remain high in some settings. It has been suggested that the pathogenesis of these cancers in HIV infected individuals is complex and different to that in HIV uninfected individuals, with the possibility that the virus may have an oncogenic role. This has already been demonstrated in the case of the HIV/AIDSdefining cancer Kaposi Sarcoma. However, the same has not been unequivocally demonstrated in HIV-associated NHL. In light of this, the mechanisms through which viruses and viral components promote cellular transformation is an area of active research. One of these mechanisms manipulated by viruses is through the dysregulation of cellular microRNAs (miRNAs) which are small non-coding RNA molecules that are key regulators of gene expression. While they are essential for normal cellular functioning, their expression has been found to be deregulated in diseases including cancer. Several studies have described specific miRNA signatures for NHLs including for DLBCL and BL but none have been described for the HIV-association of these cancers. Aim: The aim of this project was to identify and characterise miRNAs involved in the pathogenesis of HIV-associated NHLs. This thesis reports on the changes in expression of miRNAs in B-cells exposed to an attenuated form (structurally intact but non-infectious) of HIV. Methods: We designed a custom miRNA microarray to identify deregulated miRNAs in the BL cell line Ramos that were exposed to HIV compared to microvesicle treated cells. It was initially planned to use both normal B-cells (L1439A) and BL cells for analysis but Ramos was selected due to technical reasons for this step. Thereafter we validated selected miRNAs by quantitative real-time PCR (qPCR) using single-tube TaqMan® Assays which was predominantly performed in the lymphoblastoid cell line L1439A, which is derived from a healthy donor. We then focused on further characterising the role of one miRNA in the development of HIV-associated NHL by using prediction programmes to predict its putative gene targets and then confirmed its target by using qPCR and western blot analyses. Results: Extensive and comprehensive analysis of the array data led to the identification of a large number of miRNAs which were differentially expressed, with 32 being selected for further studies. These 32 miRNAs include 16 upregulated and 16 downregulated miRNAs, and were selected because they displayed changes in expression by two or more folds. Thereafter, four miRNAs, namely miR-363-3p, miR-222-3p, miR-200c-3p and miR-575, were chosen for validation based on their reported involvement in cancer for validation. The results of two miRNAs (miR-575 (upregulated) (p<0.05) and miR-200c-3p (downregulated) (p<0.05)) were found to be consistent with the results obtained from the miRNA microarray whilst the other two were opposite to that result (both downregulated) (p<0.05). Using online tools as well as the published literature, several potential target genes of miR-575 were identified, namely DENND5A, CDK1, CSTA and ATAD5. One particular target, the BH3- like motif containing inducer of cell death (BLID), which is involved in apoptosis, has previously been confirmed as a gene target in non small cell lung cancer. Using qPCR, we found that BLID messenger RNA (mRNA) was downregulated in normal B-cells when exposed to HIV-1 AT-2. Unfortunately, the BLID protein could not be detected using western blot analysis despite several attempts at detecting varying concentrations of the protein and using two different positive control cell lines. Conclusion: The reverse correlation, between miR-575 and BLID mRNA expression in the same cell line and under the same treatment conditions, supports the notion that the downregulation of miR-575 may be physiologically relevant. However, this could not be further verified as the BLID protein could not be detected in the L1439A cells, even in the microvesicle treated control cells. Future studies should look at further characterisation of miR- 575 in the pathogenesis of HIV-associated NHLs by investigating other predicted gene targets of the miRNA. This will then be followed by loss and gain of function assays to confirm the miRNA:mRNA relationship. Furthermore, functional analyses, such as measure of apoptosis, expression of key regulators of the cell cycle, and other cellular events characteristic of cancer should be carried out to define the role of the miR-575 in the development of HIV-associated lymphoma.